Information Environmentalism A Governance Framework for Intellectual Property Rights - Cunningham, Robert (Edward Elgar Publishing, 2014)
Information Environmentalism applies four environmental analytical frameworks - ecology, 'the commons', public choice theory, and welfare economics - to the information environment. The book neatly captures the metaphorical relationship between the physical environment and the information environment by alluding to the environmental philosophy of 'social ecology' and the emergent informational discourse of 'cultural environmentalism'.